Effect of Imipenem and Amikacin Combination against Multi-Drug Resistant Pseudomonas aeruginosa - Sara Mahmoud Farhan (MDPI AG, 2021)
Pseudomonas aeruginosa is an opportunistic nosocomial pathogen associated with high morbidity and mortality rates. Combination of antibiotics has been found to combat multi-drug resistant or extensively drug resistance P. aeruginosa. In this study we investigate the in vitro and in vivo effect of amikacin and imipenem combination against resistant P. aeruginosa. The checkerboard technique and time-killing curve have been performed for in vitro studies showed synergistic effect for combination. A peritonitis mouse model has been used for evaluation of the therapeutic efficacy of this combination which confirmed this synergistic effect. The in vitro and in vivo techniques showed synergistic interaction between tested drugs with fractional inhibitory concentration indices (FICIs) of ≤0.5. Conventional PCR and quantitative real-time PCR techniques were used in molecular detection of bla IMP and aac(6′)-Ib as 35.5% and 42.2% of P. aeruginosa harbored bla IMP and aac(6′)-Ib respectively. Drug combination viewed statistically significant reduction in bacterial counts (p value < 0.5). The lowest bla IMP and aac(6′)-Ib expression was observed after treatment with 0.25 MIC of imipenem + 0.5 MIC of amikacin. Morphological changes in P. aeruginosa isolates were detected by scanning electron microscope (SEM) showing cell shrinkage and disruption in the outer membrane of P. aeruginosa that were more prominent with combination therapy than with monotherapy.